FEMINISME LIBERAL DALAM NOVEL PERAHU KERTAS KARYA DEWI LESTARI - Ratna; Karman, Andi; Abidin, Aslan (STKIP Subang, 2026)
This research analyzes the manifestations of liberal feminism in Dee Lestari’s novel Perahu Kertas, focusing on the character Kugy. Utilizing a qualitative approach and feminist literary criticism, this study dissects narrative data concerning work ethic, career accessibility, and gender comparison.The results indicate that the character Kugy represents an independent subject who prioritizes rationality and personal responsibility in decision-making. The novel's narrative reflects the internalization of equal opportunity within the professional sphere, where intellectual competence eliminates the barriers of gender stereotypes. Furthermore, the professional interaction between Kugy and Keenan demonstrates a deconstruction of gender hierarchy through equal workplace synergy.The study concludes that the novel serves as a manifestation of female emancipation, positioning equal rights as a fundamental instrument for self-actualization in modern society.